Loading ...
Sorry, an error occurred while loading the content.

Re: [PrimeNumbers] Primaliy test for a series

Expand Messages
  • Jens Kruse Andersen
    ... = 2^(2n)-1 = (2^n-1)*(2^n+1) -- Jens Kruse Andersen
    Message 1 of 2 , Feb 21, 2007
    • 0 Attachment
      Christ van Willegen wrote:
      > It seems as if it's just sum(x=0,2*n,2^x) for some n,
      > or did I misread that?

      The original sum ended with odd exponent:
      > 1 + 2 + 2^2 + 2^3 + ... + 2^(2*n - 1)

      = 2^(2n)-1 = (2^n-1)*(2^n+1)

      --
      Jens Kruse Andersen
    Your message has been successfully submitted and would be delivered to recipients shortly.